Emotional responses to innovative Science teaching methods: Acquiring emotional data in a General Science teacher education class - Jesus Sanchez-Martin; Florentina Cañada-Cañada; María Antonia Dávila-Acedo (OmniaScience, 2018)
The current work tries to inquiry how different teaching methods affect on the student's emotional performance. The traditional questionnaire for data collection has been replaced by in-situ, on-line-assisted, survey. This instrument was continoulsy applied over the course of 17 General Science lessons.  The experiment involved 120 prospective primary education teachers. Emotions to choose: rejection, boredom, satisfaction, surprise and the teaching methods involved were pure oral presentation, oral presentation with gamification, oral presentation with audiovisual support, oriented research, and hands-on activities.  When the teaching method was changed to gamification or hands-on activities, the prospective teachers felt dynamic emotions, whereas they generally felt satisfaction or boredom (static emotions) with a traditional pure oral presentation.  The students mainly identified the teaching method as being the most influential reason for having chosen their prevalent emotion, reflected in a dramatic increase in emotional performance when they were taught with innovative methods.